(untitled) (Scientific journal of the Fergana State University, 2025)
The products of the interaction of chitosan with dibasic carboxylic acids are usually used to prepare solid and hydrogel membranes. In our study, we aimed to conduct the interaction of chitosan and oxalic acid in a solution environment, unlike the conditions of high temperature and shear deformation of solid substances. This reaction follows the addition/elimination mechanism, the amide function of the amino groups is restored and amides are formed. When comparing the infrared spectra, X-ray phase diffractograms, and electron microscope images of chitosan and the resulting product oxalyl chitosan, it was found that the reaction was sufficiently complete. It was found that the optimal conditions for the oxalic acid N-acylation reaction of chitosan with a deacetylation degree of 89% were 70 ºC for 24 hours, and the yield of the product obtained was 59.5%.